Saturday

April 19, 2014

April 19, 2014

Posted by **Amber** on Sunday, July 1, 2012 at 2:26am.

A. -4

B. 2

C. 24

D. 26

E. 48

- Algebra -
**Steve**, Sunday, July 1, 2012 at 6:18amg(f) = f^2 - f - 6

= (x-2) - √(x-2) - 6

g(f(6)) = 4 - 2 - 6 = -4

**Related Questions**

Algebra 1 - Am i on the right track? radical of 3 times radical of three= ...

polynomials - i also have theses to solve Factor the polynomial x2 + 5x + 6 ...

math , help,algebra - i am up to this point in my problem but i don't know what ...

Algebra - I'm adding 2(radical 50) + 12 (radical 8). I began by breaking the ...

Algebra - Given f(x) = radical x-2 and g(x) = x2 – x – 6. Find (f – g)(6). A. -...

algebra - 3 radical x - 4 radical y divided by 3 radical x - 2 radical y = ( i ...

math,correction - Simplify by combining like terms. Problem #32 radical (63) - 2...

algebra - (Radical of 5 plus radical of 2)x(radical of 5 subtract radical of 2)

Math - Symplify (radical x/8) is the answer x (radical 2)/4 i put it to be (x/2...

math - in the question 6radical x +3 radical y -2radical y +3 radical x -radical...